2021
DOI: 10.1002/adfm.202100791
|View full text |Cite
|
Sign up to set email alerts
|

A Difluoro‐Monobromo End Group Enables High‐Performance Polymer Acceptor and Efficient All‐Polymer Solar Cells Processable with Green Solvent under Ambient Condition

Abstract: In this paper, a difluoro-monobromo end group is designed and synthesized, which is then used to construct a novel polymer acceptor (named PY2F-T) yielding high-performance all-polymer solar cells with 15.22% efficiency. The fluorination strategy can increase the intramolecular charge transfer and interchain packing of the previous PY-T based acceptor, and significantly improve photon harvesting and charge mobility of the resulting polymer acceptor. In addition, detailed morphology investigations reveal that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 75 publications
2
65
0
Order By: Relevance
“…Most recently, He et al 26 reported the same strategy of configurational control with isolated IC‐Br‐γ and IC‐Br‐δ on a large scale to design new polymer acceptors, and successfully produced two regioregular narrow‐bandgap PSMAs, PBTIC‐γ‐2F2T and PBTIC‐δ‐2F2T. Their study also highlighted that precise control of the molecular configuration enhanced the charge carrier mobility and decreased the π ‐ π stacking distance, which afforded higher performance in all‐PSCs 28,32,33 . Additionally, Liu et al 32 obtained an optimal morphology, reduced nonradiative energy loss, and an impressive PCE of 16.09% in ternary all‐PSCs, where the B→N‐based polymer acceptor was incorporated into the PM6:PY‐IT (regioregular PSMA) host blend.…”
Section: Figurementioning
confidence: 95%
See 2 more Smart Citations
“…Most recently, He et al 26 reported the same strategy of configurational control with isolated IC‐Br‐γ and IC‐Br‐δ on a large scale to design new polymer acceptors, and successfully produced two regioregular narrow‐bandgap PSMAs, PBTIC‐γ‐2F2T and PBTIC‐δ‐2F2T. Their study also highlighted that precise control of the molecular configuration enhanced the charge carrier mobility and decreased the π ‐ π stacking distance, which afforded higher performance in all‐PSCs 28,32,33 . Additionally, Liu et al 32 obtained an optimal morphology, reduced nonradiative energy loss, and an impressive PCE of 16.09% in ternary all‐PSCs, where the B→N‐based polymer acceptor was incorporated into the PM6:PY‐IT (regioregular PSMA) host blend.…”
Section: Figurementioning
confidence: 95%
“…The electron‐deficient strength of terminal group in PSMAs could affect not only charge dynamics and energy levels, but also the optical absorption via the ICT effect. The halogenation and conjugation extension strategies in IC‐Br terminal group have provided the facile way to endow the resulting PSMAs (such as PYF‐T‐o and PY2F‐T) not only with a stronger ICT to broaden NIR absorption but also the increased interchain packing for high electron mobility 28,30 . Developing additional innovations (extending the conjugation or introducing the heteroatom) on the electron‐withdrawing terminal groups than fluorinated or chlorinated IC‐Br terminal groups is also a potential approach for further advancing PSMAs.…”
Section: Design Of Psmasmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they synthesized PY2F-T by adopting a difluoro-monobromo end group, IC-2FBr. The performance of PY2F-T-based devices was improved significantly by the fluorination strategy, delivering a device PCE of 15.22% [ 75 ]. Recently, Fu and co-workers developed a series of PZTs as acceptors for all-polymer solar cells based on the benzotriazole-core fused-ring segment.…”
Section: D-a Materialsmentioning
confidence: 99%
“…Based on PYF-T, Yu and coworkers [90] in 2021 reported a PY2F-T with two fluorine atoms on its one end group, and an all-polymer solar cell with an efficiency of 15.22% [90] was obtained. After introducing the fluorine-free PYT as the third component into the main system of PM6: PY2F-T by Sun and coworkers [91], the improved PCE of PM6:PY2F-T is as high as 17.2% [91] due to a balance between material crystallization and phase separation.…”
Section: Polymer Acceptormentioning
confidence: 99%